Explore Westonci.ca, the premier Q&A site that helps you find precise answers to your questions, no matter the topic. Discover in-depth solutions to your questions from a wide range of experts on our user-friendly Q&A platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.

How do I simplify the 6th root of 4 divided by the 3rd root of 4?

Sagot :

so remember some exponentional laws

[tex]x^{m/n} = \sqrt[n]{x^m}[/tex]

 [tex] \frac{x^n}{x^m}=x^{n-m} [/tex] and

[tex] x^{-n}= \frac{1}{x^{n}} [/tex]
so
 
4 to the 6th root=4^(1/6)
4 to the 3rd root=4^(1/3)

so
[tex] \frac{4^{1/6}}{4^{1/3}} =4^{(1/6)-(1/3)}=4^{(1/6)-(2/6)}=4^{-1/3}[/tex]
and  [tex] 4^{-1/3}= \frac{1}{4^{1/3}}= \frac{1}{ \sqrt[3]{4} } [/tex]

the answer is [tex] \frac{1}{ \sqrt[3]{4} } [/tex]